1978
DOI: 10.1126/science.663630
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite and Nitrate Are Formed by Endogenous Synthesis in the Human Intestine

Abstract: Studies of nitrate balance in humans and analyses of fecal and ileostomy samples indicate that nitrite and nitrate are formed de novo in the intestine, possibly by heterotrophic nitrification. These findings significantly alter our previous conceptions of human exposure to nitrite and suggest an even wider role for nitrite in the etiology of human cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
77
1
5

Year Published

1979
1979
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 270 publications
(88 citation statements)
references
References 19 publications
4
77
1
5
Order By: Relevance
“…The association between endogenous production of nitric oxide radical, as mediated by macrophages, involved in the infectious and inflammatory response has been a topic of interest and toxicologic research for more than 10 years (43)(44)(45)(46)(47)(48). Debate remains concerning the significance and amount of this endogenous nitric oxide production in terms of the organism's overall oxidative stress (49,50).…”
mentioning
confidence: 99%
“…The association between endogenous production of nitric oxide radical, as mediated by macrophages, involved in the infectious and inflammatory response has been a topic of interest and toxicologic research for more than 10 years (43)(44)(45)(46)(47)(48). Debate remains concerning the significance and amount of this endogenous nitric oxide production in terms of the organism's overall oxidative stress (49,50).…”
mentioning
confidence: 99%
“…Many studies have been devoted to problems related to the fate of ingested nitrate and nitrite in the body (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). It is certain from the literature that increased ingested nitrate or nitrite results in increased urinary excretion of nitrate and nitrite, but the details of the major metabolic pathway are not sufficiently known.…”
Section: Absorption and Conversion Of No In Bloodmentioning
confidence: 99%
“…Tannenbaum et al (33) suggested that nitrate and nitrite are produced de novo in the intestine as a result of heterophic nitrification. According to the research of Witter et al (34), who studied 1NO in humans and rats, the 13N compound administered was not rapidly absorbed through the stomach wall; the concentration was increased in the lower intestine, and a portion of the 13N was retained in the body.…”
Section: Absorption and Conversion Of No In Bloodmentioning
confidence: 99%
“…A number of studies have now established that mammals on low nitrate diets excrete more nitrate than they ingest (1)(2)(3). At first it was thought that this excess urinary nitrate was the product of intestinal microbial metabolism (1), but subsequent studies with germ-free and conventional rats showed that the process of nitrate biosynthesis was by a mammalian pathway (2).…”
mentioning
confidence: 99%